Research on the Training of Reserve Football Talents at Home and Abroad - On the Strategy of Training Reserve Football on Campus - Bo Jiang; Shaojie Wang; Qiuyi Chen; Jinbo Xiang (Nicolaus Copernicus University in Toruń, 2024)
This research takes the training strategy of reserve football talents on campus as the research object, and takes the literature method and logical analysis method as the research method to analyze and discuss the drawbacks of the existing strategy of reserve football talents training on campus in China and to integrate with the international standards, and to dig deeply into the problems of the current training strategy of reserve football talents under the current mode. Theoretical Significance: Exploring the strategy of combining teaching and sports with training of reserve football talents on campus is to promote the wider, deeper and healthy development of youth football in China, to promote the healthy growth of young students, to consolidate the football foundation of our country, to cultivate more excellent football talents, to provide a theoretical basis for the construction and development of football schools with Chinese characteristics, and to provide a theoretical reference for our schools. The sustainable development of football has laid a good theoretical foundation. Practical Significance: Football itself is an important part of school education and an inevitable requirement to promote students'all-round development. Through the training strategy of reserve football talents on campus, we can develop teenagers' football on campus, cultivate students'interest in football, cultivate students' good will quality and expand students'participation in football. On the basis of the intensity of football training on campus, we find new seedlings of football, further improve their football skills and level, effectively improve the quantity and quality of football reserve talents on campus, train high-quality football talents for the country, and fully demonstrate the practical significance of implementing the strategy of training football reserve talents on campus.